Algoritma Pengembangan Sistem Informasi Kepegawaian Menggunakan Metode Prototype - Pradipta, Rahman; Bahri, Rahmad (Universitas Islam Negeri Sumatera Utara, 2025)
Digital transformation in human resources (HR) functions encourages organizations to replace manual administration with web-based HR information systems to improve data integration, security, and decision-making speed. However, implementing HR systems that still rely on hardcopy files or spreadsheets faces various challenges, such as the risk of data loss, inconsistent updates, weak access control, and delays in HR services. From a software engineering perspective, the prototype method is considered effective in addressing requirement uncertainties because it allows user involvement through continuous iteration and feedback. This study aims to (1) design and implement an HR information system development algorithm using the prototype method and (2) quantitatively evaluate the impact of prototyping iterations on system quality, including usability, security, and flexibility, as well as its impact on the effectiveness of HR processes. The study used a quantitative approach with descriptive analysis based on a Likert scale to measure users' perceptions of system quality. The results showed that prototyping iterations positively contributed to improving system quality and supported the effectiveness of HR services, particularly in accelerating administrative processes and reducing operational errors. These findings reinforce the role of the prototype method as a relevant development approach for web-based personnel information systems. Keywords: Personnel Information System, Prototype Method, System Quality, Human Resource Effectiveness, Software Engineering.